Translational Capacity of a Cell Is Determined during Transcription Elongation via the Ccr4-Not Complex - Gupta Ishaan (CELL REPORTS, 2016)
The current understanding of gene expression considers transcription and translation to be independent processes. Challenging this notion, we found that translation efficiency is determined during transcription elongation through the imprinting of mRNAs with Not1, the central scaffold of the Ccr4-Not complex. We determined that another subunit of the complex, Not5, defines Not1 binding to specific mRNAs, particularly those produced from ribosomal protein genes. This imprinting mechanism specifically regulates ribosomal protein gene expression, which in turn determines the translational capacity of cells. We validate our model by SILAC and polysome profiling experiments. As a proof of concept, we demonstrate that enhanced translation compensates for transcriptional elongation stress. Taken together, our data indicate that in addition to defining mRNA stability, components of the Ccr4-Not imprinting complex regulate RNA translatability, thus ensuring global gene expression homeostasis.